NEW PEDAGOGICAL TECHNOLOGIES IN TEACHING ENGLISH LANGUAGE TO STUDENTS WITH NO SPECIALIZED FOREIGN LANGUAGE (American Journal of Pedagogical and Educational Research, 2022)
Ensuring the quality of teaching foreign languages to the young generation, fundamentally improving the system of training specialists who can speak foreign languages fluently, training mature personnel who meet world educational standards by mastering foreign languages in our country is one of the goals of the education reform. Identifying opportunities in language teaching and bringing them to life, the teacher's knowledge, creativity, the ability to arouse students' love for their subject, and the establishment of a cooperative relationship with students are the requirements of the current era. The decision to further develop foreign language teaching, implement measures to improve the level and quality of training of qualified teachers who have a high level of foreign language skills for general education schools, vocational colleges and academic lyceums, higher education institutions in accordance with international standards. was adopted in order to provide. At the same time, it should be said that each language being studied has its own rules and secrets. In order to become a mature specialist who meets international standards, the learner